The Diversity of Famlily Lauraceae Juss. in Pu Mat National Park, Nghe An Province - Dai, Do Ngoc; Huong, Le Thi; Chau, Dao Thi Minh; Cuong, Nguyen Tien; Truong, Nguyen Cong; Hong, Le Thi (VNU Journal of Science: Natural Sciences and Technology, 2021)
This paper presents some results of research on family Lauraceae in Pu Mat National Park, Nghe An province, from 2015 to 2017. Total 90 species belonging to 13 genus of Lauraceae family were collected and identified. There were1 genera and 22 species found as new records for the plant list of Pu Mat published in 2017. Cinnamomum was the richest genus (26 species), then followed by Litsea (24 species), Lindera (8 species), and other genera (1 to 6 species). In Lauraceae of Pu Mat National Park there are 4 threatened species listed in the Red Data Book of Viet Nam (2007) are Cinnamomum parthenoxylon, Actinodaphne elliptibacca, Cinnamomum balansae, Cinnamomum cambodianum. The number of useful plant species of the Lauraceae is categorized as follows: 60 species for timber, 50 species supply essential oil, 34 species as medicinal plants, 13 species for ornamental, 3 species for edible and ornamental. The Spectrum of Biology (SB) of the Lauraceae in Pu Mat is summarized, as follows: Ph% = 11.11%Mg + 50.00%Me + 36.67%Mi + 1.11%Na + 1.11Pp. The Lauraceae in Pu Mat National park are mainly comprised of the tropical element (37.78%), endemic element (57.78%), temperate element (2.22%) and crops element (2.22%).